You majored in what? : mapping your path from chaos to career - Brooks, Katharine (New York : Plume, 2010)
Provides information on job hunting and having a successful career using the Wise Wandering system.
'With a new section on job hunting in a recession'-- Cover.
Includes bibliographical references (p. 307-310) and index.
Keywords: Job hunting -- United States; Employment interviewing -- United States; College graduates -- Employment -- United States; College majors -- United States